Спектральні характеристики акустичного випромінення малих багатороторних БПЛА - Гапонов, Є. Ю. (ХНУРЕ, 2020)
The results of experiments on the detection of drones by acoustic signals are processed. The purpose of the study is to identify the characteristic features of the acoustic radiation spectra of UAVs in comparison with other sources of noise. The acoustic radiation of the DJI Phantom 2 quadcopter has been investigated. The spectra have pronounced harmonic components with frequencies multiple of the screw speed. In the case of large divergence of modes of quadcopter engines the spectral maxima are divided into several, which may be one of the characteristics for the classification of UAVs.
Keywords: акустичне випромінення; БПЛА